Effects of exsolution on the stability and morphology of Ni nanoparticles on BZY thin films. (15th April 2022) - Jennings, Dylan; Ricote, Sandrine; Santiso, José; Caicedo, José; Reimanis, Ivar
Graphical abstract: Abstract: Yttria doped barium zirconate (BZY) is of interest for use as a catalyst support material, supporting exsolved Ni nanoparticles. Exsolution has been hypothesized to impart catalytic nanoparticles with exceptional resistance to particle coarsening, a known degradation mechanism in catalysts. However, the mechanisms and kinetics of Ni nanoparticle coarsening in BZY are unknown. This work analyzes the kinetics of the coarsening of exsolved Ni nanoparticles on epitaxial BZY thin films at three temperatures (600, 700, and 800  ∘ C) over a time span of 150 h. It is demonstrated that Ni coarsening transitions from an Ostwald ripening process to particle migration and coalescence after Ni particles reach a critical size. The coarsening behavior of BZY/Ni is shown to be dependent on the BZY surface orientation, with Ni particles on (111) oriented thin films coarsening the least. The preferred orientation relationships between Ni and BZY on (100), (110), and (111) oriented films are determined. Additionally, the morphology of Ni particles produced through exsolution and thin film dewetting are compared, showing that the socketing behavior and interfacial energy are independent of the Ni particle preparation method.